Externalities, clusters and economic growth: The Cluster Policy Paradox - Argentino Pessoa (European Regional Science Association (ERSA), 2011)
The literature on clustering has highlighted several advantages of industrial agglomerations. Persons and firms benefit from the production and innovation activities of neighbouring companies in the same and related industries. Considering such benefits, which are viewed as positive externalities, Michael Porter argues that clustering is an important way for firms fulfilling their competitive advantages and for rising regional and national competitiveness. So, it is opportune to ask: what is the appropriate policy for maximizing the benefits of CE (cluster externalities)? There are basically two possible replies to the above question: on the one hand, the traditional optimal-policy perspective recommends providing a subsidy to firms generating CE, with the subsidy adjusted for equalizing the strength of the externality; on the other, a more pragmatic perspective based on Porter's policy prescriptions. However, the evidence shows a paradox: policy makers use the competitiveness rhetoric inspired in the competitive advantages of Porter but, in practice, they go on using the industrial targeting that was also criticized by Porter. In this paper we deal with this paradox proving that despite the extensive amount of externalities is the traditional comparative advantage approach that must guide policy. This finding is congruent with the Porter's policy prescriptions and has clear implications in regional policy allowing to support the answer to the following question: Must policy be focused on creation of new clusters in activities that have verified large positive effects elsewhere or, conversely, on developing the traditional activities in region, which allegedly have shown lower externalities? But the answer to this question depends on our comprehension of industrial aggregation processes, which implies the full understanding of concepts as clusters and externalities. So, the remainder of this paper is organized as follows. After reflecting on the concept of cluster in section 2, section 3 deals with the different type of externalities present in industrial agglomerations. Section 4 considers the existence of dynamic externalities and relates them with the advantages of backwardness. Section 5 uses a model that includes various types of externalities in order to draw lessons for guiding clustering policy. Finally, section 6 concludes.
Keywords: 330